2015
DOI: 10.1038/srep10827
|View full text |Cite
|
Sign up to set email alerts
|

Characterizations of individual mouse red blood cells parasitized by Babesia microti using 3-D holographic microscopy

Abstract: Babesia microti causes “emergency” human babesiosis. However, little is known about the alterations in B. microti invaded red blood cells (Bm-RBCs) at the individual cell level. Through quantitative phase imaging techniques based on laser interferometry, we present the simultaneous measurements of structural, chemical, and mechanical modifications in individual mouse Bm-RBCs. 3-D refractive index maps of individual RBCs and in situ parasite vacuoles are imaged, from which total contents and concentration of dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(64 citation statements)
references
References 47 publications
(76 reference statements)
2
62
0
Order By: Relevance
“…Previously, ODT has been widely used to study various biological samples including red blood cells [15][16][17][18][19][20][21][22] however, we were unable to identify lymphocyte cell types due to their indistinguishable cellular morphology and biochemical characteristics.…”
Section: Identification Of Lymphocyte Cell Types Is Crucial For Undermentioning
confidence: 84%
See 1 more Smart Citation
“…Previously, ODT has been widely used to study various biological samples including red blood cells [15][16][17][18][19][20][21][22] however, we were unable to identify lymphocyte cell types due to their indistinguishable cellular morphology and biochemical characteristics.…”
Section: Identification Of Lymphocyte Cell Types Is Crucial For Undermentioning
confidence: 84%
“…Previously, ODT has been widely used to study various biological samples including red blood cells [15][16][17][18][19][20][21][22] , white blood cells (WBC) 23,24 , hepatocytes 25 , cancer cells 16,[26][27][28][29][30][31][32] , neurons 32,33 , bacteria 34,35 , phytoplankton 36 , and hair 37 . In our previous study, we reported that ODT enables the quantitative analysis of WBCs including lymphocytes and macrophages 23 .…”
mentioning
confidence: 99%
“…According to the literature Babesia microti penetrates directly into erythrocytes without the stages of initial proliferation at other organs [5,21].This feature is related to the specifi city of the impact of the membrane of red blood cells with a particular species of piroplasm [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, other RBC infecting microbes can be investigated, such as Babesia microti, which is an obligate parasite in humans, hamster, and mouse. To find alternatives to methods requiring experience of professional technicians, usually based on optical microscope with Giemsa-stained blood smears, DH methodology was exploited [50]. The authors found the technique to be useful for determining morphological modifications in host RBCs, quantifying contents, and concentration of the cellular dry mass, as well as dynamic membrane fluctuations measured at the individual cell level, which are in turn strongly correlated with the mechanical deformability of cell membrane.…”
Section: Blood Cell Screeningmentioning
confidence: 99%